A Study of Emotional Intelligence among Secondary School Students in Relation to Academic Anxiety and Adjustment - Ahuja, Amit (JOURNAL OF INDIAN EDUCATION, 2016)
The aim of the present paper is to probe emotional intelligence, academic anxiety and adjustment among students at the secondary school level. Random sampling was exercised in the selection of sample, which comprised 100 boys and 100 girls of Class IX in two government schools in Delhi state. Emotional Intelligence scale (Singh and Narain, 2014), Academic Anxiety Scale (Singh and Sen Gupta, 2013) and Adjustment Inventory for School Students (Sinha and Singh, 2013) were used as tools for data collection. The collected data was analysed by t-test and Karl Pearson’s Coefficient of correlation (r). It was found that girls had higher emotional intelligence scores than boys but in adjustment, boys significantly outperformed girls. There was no statistically significant difference between both the genders with respect to academic anxiety. Further, emotional intelligence and academic anxiety were not significantly related. However, a statistically significant positive correlation was found between emotional intelligence and adjustment of students. Also, academic anxiety was negatively co-related to adjustment of secondary school students.